Values of Hungarian pigeon breeding - Bagi, Zoltán; Kusza, Szilvia (Acta Agraria Debreceniensis, 2014)
Pigeon breeding has a history dating back several centuries in Hungary. It has internationally renowned and accepted results. Our aim was to estimate the range of values related to Hungarian pigeon breeding and draw attention to the importance of their conservation. We studied the biological values of native breeds and the appearance of pigeon breeding within the Hungarian culture. These include the use of the symbol, the relating beliefs and customs, language, gastronomy, architecture and object values, as well as the community-building effect. Based on our results we can say that this topic is worthy of further research.